2011
DOI: 10.1111/j.1467-8535.2011.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the Facebook group as a learning management system: An exploratory study

Abstract: Facebook is a popular social networking site. It, like many other new technologies, has potential for teaching and learning because of its unique built-in functions that offer pedagogical, social and technological affordances. In this study, the Facebook group was used as a learning management system (LMS) in two courses for putting up announcements, sharing resources, organizing weekly tutorials and conducting online discussions at a teacher education institute in Singapore. This study explores using the Face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
318
1
28

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 492 publications
(363 citation statements)
references
References 27 publications
16
318
1
28
Order By: Relevance
“…Based on the students' responses, it appears that most students use social networks as a means of communication. This result is consistent with studies carried out in Singapore (Wang et al, 2012), which have shown that Facebook enables students to communicate and interact with their peers easily, as it appears to be a good tool for supporting communication and social interaction.…”
Section: Results Analysis and Reflectionsupporting
confidence: 81%
See 3 more Smart Citations
“…Based on the students' responses, it appears that most students use social networks as a means of communication. This result is consistent with studies carried out in Singapore (Wang et al, 2012), which have shown that Facebook enables students to communicate and interact with their peers easily, as it appears to be a good tool for supporting communication and social interaction.…”
Section: Results Analysis and Reflectionsupporting
confidence: 81%
“…Finally, the results of this study are consistent with findings in other studies (Beurer-Zuellig & Meckel, 2008;Clough et al, 2008;Thirunarayanan et al, 2011;Uys et al, 2012;Wang et al, 2012), as they highlight the advantages provided by technologies: a) for collaborative work, given their potential for use almost anywhere and at any time;…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The use of Facebook for learning and its educational value has received much attention (see review by Manca & Ranierit, 2013). This debate shifts between the more formal approaches of Facebook as a proxy Learning Management System (LMS) (Wang et al, 2012), to the informal use of the site for collaborative classroom activities . Research on student views of Facebook as a learning tool has primarily found that it is first and foremost used for social purposes, sometimes used for informal learning or student-to-student discussions of academic matters but rarely (if ever) for formal teaching purposes between staff and students involving formal assessment (Madge et al, 2009).…”
Section: Facebook In the Lives Of Undergraduate Studentsmentioning
confidence: 99%